Analgesic effect of gabapentin in patients with carpal tunnel syndrome - Reza Sabet, Karamatollah Rahmanian, Abdolreza Sotoodeh Jahromi, Abdolhossein Madani (Journal of Applied Pharmaceutical Science, 2017)
Introduction: Carpal tunnel syndrome (CTS) is a common condition that caused by entrapment of the median nerve in the wrist of hand. The aim of study was to assess the antinoceceptive effect of gabapentin in patients with CTS.Materials and Methods: We conducted a clinical trial recruiting patients with mild CTS for a period of more than three months. Fifty patients were enrolled in the study, of who 25 were randomly assigned togroup A and 25 to group B. CTS confirmed by electrophysiological tests. Patients in the group A received naproxen (starting dose 500 mg once daily PO) and in the group B received combination therapy; gabapentin (starting dose 100 mg once daily to a target of 300 mg daily PO) and naproxen (starting dose 500 mg once daily PO). Primary end-point was the symptom severity scale (SSS) and functional state scale (FSS) which was measured at baseline and two months after treatment.Results: There was no significant difference in baseline variables between the two treatment groups. Both groups produced significant improvement in symptoms at two months after treatment. The SSS and FSS at the end of two months was statistically significant difference in both study groups than before treatment. Also by two months, the mean reduction in SSS and FSS scale on group B was significant when compared with group A (p < 0.001). Conclusions: Combination therapy of Gabapentin and naproxen produced a significant reduction in symptom severity and functional state scale compared with naproxen alone over a two month period.
Keywords: CTS, Gabapentin, Naproxen, SSS Scale, FSS Scale.